(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Medical education is a continuously evolving field that requires faculty members to engage in ongoing professional development to maintain high-quality instructions. Faculty development programs at medical education department of medical colleges play a critical role in equipping educators with the necessary skills to address the dynamic challenges of medical education. However, the effectiveness of such programs is contingent upon accurately identifying faculty training needs. This study aimed to conduct a comprehensive need assessment survey to determine the specific areas where faculty members require further development in order to improvise their teaching skills. Methods The study was conducted at College of Medicine, King Faisal University, Al-Ahsa. A structured google survey was designed and developed to assess faculty training needs across various competencies, including teaching methodologies, clinical instruction, curriculum development, and educational research. Faculty members were asked to rate the importance of each competency and indicate their need for additional training. The survey was distributed to all faculty members of college of medicine, King Faisal University, Al-ahsa by email. 41 faculty members across different departments, including Surgery, Biomedical Sciences, Clinical Neurosciences, and Obstetrics and Gynecology responded to the survey. Data collection was conducted over one month, and responses were analyzed using descriptive statistics. Results The survey yielded responses from 41 faculty members, with Assistant Professors constituting 70% of the participants. The highest departmental representation was from Biomedical Sciences (35%) and Surgery (25%). Teaching in large and small groups received the highest mean importance rating (4.5), followed by facilitating and managing learning (4.3). The most frequently reported areas requiring additional training included large group teaching (65%), assessment and learning (60%), and educational research (55%). Faculty members recommended regular workshops on teaching methodologies, educational research, and statistical analysis, with an emphasis on accreditation of training sessions through relevant health authorities. Discussion The findings highlight the critical need for faculty development in large group teaching, student assessment, and educational research. The increasing role of technology in medical education was also evident, as faculty members expressed a need for training in e-learning platforms. Need assessment surveys provide valuable insights for tailoring faculty development initiatives; however, their limitations must be acknowledged. Surveys may not capture all faculty challenges due to reliance on self-reported data, potentially leading to a narrow focus on training programs. To address these limitations, institutions should integrate qualitative methods such as focus groups and peer mentoring to supplement survey findings. The integration of interdisciplinary faculty development initiatives has the potential to augment collaborative efforts and elevate the quality of educational experiences. Conclusion: This need assessment survey provides essential insights into the training needs of faculty members, emphasizing the importance of structured and targeted faculty development programs. While need assessment surveys serve as a foundational tool for shaping faculty training initiatives by the Faculty Development Committee, Medical institutions must adopt a multifaceted approach that includes qualitative insights and collaborative strategies to ensure comprehensive professional development of faculty members and other staff. By fostering an inclusive and dynamic faculty development culture, medical institutions can enhance teaching effectiveness and improve overall educational outcomes. The study helped a lot in development of annual faculty training need for the college of medicine, King Faisal University, Al-Ahsa BJMS, Vol. 25 No. 01 January’26 Page : 297-304